Hip-Hop Hustle - Jake Maddox (Stone Arch Books, 2024)
Chery Etienne has her own hip-hop dance crew, but now some of them are moving away and she will have to try out for her middle school's hip-hop dance team, although since she has never had any formal training she is not sure her unique style will be welcome.
Keywords: Sport Stories -- Sport Stories